Assessment of The Impact of Shadow Education Activities on Social Justice in The Turkish Education System - Özdemir, Sinan; Çelik, Sabri (Technium Social Sciences Journal, 2025)
The purpose of this study is to determine the effects of shadow education activities on social justice in the Turkish education system based on the opinions of school administrators and teachers. The research is a qualitative study using a descriptive survey model conducted to determine the current situation regarding how and in what direction shadow education activities affect social justice in Turkey, based on the opinions of school administrators and teachers working in public primary and secondary education institutions. The study utilized the case study design from qualitative research designs. Content analysis was used in the analysis of the data. The study group consisted of a total of 40 participants, including 25 male and 15 female participants, who were school administrators and teachers working in public primary and secondary education institutions in the central district of Kastamonu province and the districts of Daday, Devrekani, and Seydiler during the 2022-2023 academic year. Of these participants, 14 school administrators (2 school principals, 1 assistant principal, and 11 vice principals) and 26 teachers formed the working group. Different sampling methods were used in the study, such as "purposive sampling," "convenience sampling," and "maximum diversity sampling." Data were collected through face-to-face, individual interviews using the interview method. A semi-structured interview form developed by the researcher was used as the data collection tool. MAXQDA 2024 qualitative data analysis software was used to analyze the data. The research results revealed that shadow education has both positive and negative reflections on the phenomenon of social justice. In this context, the positive reflections of shadow education on social justice include "Access and opportunity equality," "Academic gains," "Empowerment and self-efficacy," "Social and personal development," and "Policies that ensure social balance and access justice to shadow education." The negative reflections include "Access and opportunity inequality," "Academic losses," "Systemic and political barriers," "Social and psychosocial negativity," and "Powerlessness and self-inadequacy." Based on the findings reached under the relevant theme headings within the scope of the research, it was concluded that social policy initiatives such as educational assistance for children from families disadvantaged in accessing shadow education are necessary. It is also deemed necessary to increase budget allocations for education and implement lifelong policies that will raise families’ living standards and establish social justice by minimizing class inequality and segregation.